Mendelian randomization analysis does not reveal a causal association between migraine and Meniere’s disease - Zhang, Kangjia; Zhang, Yong; Wu, Weijing; Lai, Ruosha (Frontiers in Neurology, 2024)
Background: According to observational research, migraine may increase the risk of MD. The two have not, however, been proven to be causally related. Methods: Using Mendelian random (MR) analysis, we aimed to evaluate any potential causal relationship between migraine and MD. Methods: We extracted single nucleotide polymorphisms (SNPs) from the European Individual Large genome-wide association studies (GWAS) relating to migraine and MD. The main technique used to evaluate effect estimates was inverse variance weighting (IVW). To assess heterogeneity and pleiotropy, sensitivity analyses were carried out using weighted median, MR-Egger, simple mode, weighted mode, and MR-PRESSO. Results: There was no discernible causative link between genetic vulnerability to MD and migraine in the random-effects IVW method(OR = 0.551, 95% CI = 0.003-110.112, P = 0.825). The extra weighted median analysis (OR = 0.674, 95% CI =0.001-723.772, P = 0.909), MR-Egger (OR = 0.068, 95% CI = 0.000-81612999.486, P = 0.806), Simple mode (OR = 0.170, 95% CI = 0.000-4356.079, P = 0.737), and Weighted mode (OR = 0.219, 95% CI = 0.000-1245.466, P = 0.760) all showed largely consistent results. Conclusions and Significance: This Mendelian randomization study provides causal evidence that Migraine is not a risk factor for MD.